Prosthetic Management of Post-surgical defect in the Mandible following Marsupialization: A Case Report - Gurung, A; Mathema, S R.B.; Maskey, B; Shrestha, K; Pandey, B; Adhikari, A; Dhyako, N; Subedi, S (Journal of Nepalese Prosthodontic Society, 2020)
Marsupialization is a conservative surgical approach for the surgical management of large odontogenic lesions. Such procedure often results in a post-surgical defect in the form of an intraoral opening. The patency of such defect, if not maintained can result in food accumulation which may lead to infection and thus delayed healing of the defect. Obturator is one of the modalities to facilitate closure of the resultant defect. This report presents a case where an acrylic plug obturator retained with clasp, was provided to the patient for the interim period following marsupialization on the mandibular left posterior region.